THE RIPPLE EFFECTS OF DISASTER-INDUCED DISPLACEMENT ON HIGHER EDUCATION STUDENTS: MIGRANT EXPERIENCES IN KHYBER PAKHTUNKHWA (Contemporary Journal of Social Science Review, 2025)
This study examines the impact of disaster-induced displacement on higher education students in Khyber Pakhtunkhwa (KP), Pakistan. The study focuses on displaced students affected by natural disasters and conflict to understand the challenges they face in continuing their learning, the support universities provide for their students, and the coping methods they use to handle their academic and social difficulties. It employed a qualitative approach, involving semi-structured interviews with 20 students displaced from different regions. Themes of the interview data not only indicated the harm in infrastructure but also disruptive and damaging situations regarding education, such as more limited access to learning options and psychological distress from displacement. Other significant barriers on the institutional level in the support systems for mental health and academic accommodations. Despite those challenges, displaced students resisted those circumstances through social support and their own coping strategies and resilience. The results suggest that colleges should strive to create comprehensive support programs tailored to the needs of students displaced in their college (or other institutions of higher education), emphasising the importance of educational flexibility, psychological well-being, and access to academic resources. The present study contributes to the body of literature examining educational displacement and offers recommendations for enhancing university policies and practices to support displaced students.